Adv
Deepak Bora
  • 0

Quadratic equations

  • 0

Find the roots of the equation x2 – 3x – m (m + 3) = 0, where m is a constant

Share

Related Questions

1 Answer

  1. ∴  x = 3+3+2m/2

    x = 6+2m/2

    x = 3+m

    & Another value of x = 3-3-2m/2

    x = -2m/2

    x = -m

     

    • 0
Leave an answer

Leave an answer

Browse

Choose from here the video type.

Put Video ID here: https://www.youtube.com/watch?v=sdUUx5FdySs Ex: "sdUUx5FdySs".

Captcha Click on image to update the captcha.